Mapping QTL for resistance against Pyrenophora tritici-repentis in wheat - Simón, María Rosa (2015)
Tan spot, caused by the fungus Pyrenophora tritici-repentis (Died.) Drechs is an important foliar disease of wheat (Triticum aestivum L.). From a set of phenotypically and molecularly characterized set of Argentinean isolates, two isolates H0019 and H0120 which do not correspond to known races of the pathogen were selected. Segregation for resistance among a set of recombinant inbred lines bred from the cross 'W7984' × cv. 'Opata 85' was used to identify the basis for resistance at the seedling stage, against those fungal isolates (H0019 and H0120), across three independent environments. On the basis of the mean performance across all three environments, a QTL against chlorosis located on the 6AS and linked to the RFLP locus Xksuh4c was significant for both isolates (with a LOD of 3.76 for isolate H0019 and 5.87 for H0120).